A survey on design of reaction spheres and associated speed and orientation measurement technologies. (April 2020) - Zhang, Jie; Yuan, Liming; Chen, Si-Lu; Liang, Yusheng; Huang, Xiaolu; Zhang, Chi; Yang, Guilin
Abstract: With the rapid development of micro-spacecraft, miniaturization has become a key problem in attitude control. As an angular momentum exchange actuator, a single reaction sphere can generate multi-DOF output torques and satisfy the requirement of three-axis attitude control. This enables it to be a potential alternative for micro-spacecraft attitude control system. Categorized by the driving principles, the various design techniques of reaction spheres are firstly reviewed, including the spherical motor based and the multi-driving-wheels based. Their advantages and disadvantages are summarized. In order to realize the closed-loop control of the reaction sphere, the techniques of measuring the speed and orientation of the reaction spheres are subsequently reviewed. These include rotary encoders or gyroscope with gimbal guideway, photoelectric encoding ring, machine vision, Hall sensor, color sensor and piezoelectric sensor. By promoting the popularization of the concept of reaction spheres, it is expected to provide new ideas for the miniaturization design and attitude control of micro-spacecraft. Graphical abstract: Highlights: The current designs of reaction spheres are reviewed, whose driving methods are categorized into spherical motors and multi-driving-wheels. The speed and orientation measurement methods of the reaction spheres are reviewed, which are essential for their real-time control. Permanent magnet reaction spheres have advantages of miniaturization and low energy consumptions among all the driving methods, combined with Hall sensors and optical mouse sensors for feedback control.